mTOR inhibition is most beneficial after liver transplantation for hepatocellular carcinoma in patients with active tumors - Schnitzbauer, Andreas; Filmann, Natalie; Adam, René; Bachellier, Philippe; Bechstein, Wolf Otto; Becker, Thomas; Bhoori, Sherrie; Bilbao, Itxarone; Brockmann, Jens; Burra, Patrizia; Chazoullières, Olivier; Cillo, Umberto; et al. (Annals of surgery, 2020)
Objective: - The aim of this study was to evaluate the survival benefit of sirolimus in patients undergoing liver transplantation (LT) for hepatocellular carcinoma (HCC) (exploratory analysis of the SiLVER-trial). - Summary and Background Data: - Patients receiving LT) for HCC are at a high risk for tumor recurrence. Calcineurin inhibitors have shown evidence to promote cancer growth, whereas mammalian target of rapamycin (mTOR) inhibitors like sirolimus have anticancer effects. In the SiLVER-trial (Clinicaltrials.gov: NCT00355862), the effect of sirolimus on the recurrence of HCC after LT was investigated in a prospective randomized trial. Although the primary endpoint of improved disease-free survival (DFS) with sirolimus was not met, outcomes were improved for patients in the sirolimus-treatment arm in the first 3 to 5 years. To learn more about the key variables, a multivariate analysis was performed on the SiLVER-trial data. - Patients and Methods: - Data from 508 patients of the intention-to-treat analysis were included in exploratory univariate and multivariate models for overall survival (OS), DFS and a competing risk analysis for HCC recurrence. - Results: - Sirolimus use for ≥3 months after LT for HCC independently reduced the hazard for death in the multivariate analysis [hazard ratio (HR): 0.7 (95% confidence interval, CI: 0.52-0.96, P = 0.02). Most strikingly, patients with an alpha-fetoprotein (AFP) ≥10 ng/mL and having used sirolimus for ≥3 months, benefited most with regard to OS, DFS, and HCC-recurrence (HR: 0.49-0.59, P = 0.0079-0.0245). - Conclusions: - mTOR-inhibitor treatment with sirolimus for ≥3 months improves outcomes in LT for HCC, especially in patients with AFP-evidence of higher tumor activity, advocating particularly for mTOR inhibitor use in this subgroup of patients. - Clinical Trial Registration: - EudraCT: 2005-005362-36 - Clinicaltrials.gov: - NCT00355862.
Gesehen am 16.03.2021